CORRELATION BETWEEN FOREIGN ENGLISH SECOND LANGUAGE (ESL) TEACHERS’ REASONS TO TEACH IN THAILAND AND THAI STUDENTS PERCEPTIONS TOWARDS ESL TEACHERS - Rigter, Bart L.M.B (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2020)
Careful attention should be given to the individual motivations of foreign native and non-native ESL teachers wanting to teach a variety of subjects using the English language as the language of instruction at Thai educational organizations. Schools should, apart from looking at the basic qualifications of a teacher, also look at what are the motivational factors which drive the teacher to teach in Thailand. The motivational factors which are the driving force behind the teacher will influence the student’s approval rates of the teacher, and as such can lead to more meaningful learning experiences for the students. The results of this research revealed that students could vividly recall both the best and worst teachers, and could provide rhyme and reason as to why the students were thinking in that manner. Furthermore, traveling teachers, teachers who would only stay at the school for one or two terms, were not memorable to the students, and as such didn’t have any proven positive or negative impact on the students.